Evaluation of epidemiological, clinical, and microbiological features of vulvovaginal candidiasis - Faraji, Reza; Maleki, Abbas; Gheisoori, Abbas; Rashidi, Taha; Salimi Mansouri, Amirhossein; Rashidi, Fatemeh; Faraji, Sadegh; Kashefizadeh, Alireza; Bozorgomid, Arezoo (GMS Hygiene and Infection Control)
Background: Vaginal candidiasis is induced by abnormal growth of yeast on the mucous membranes of the female genital tract. Approximately 75% of women experience a yeast infection once in their lifetime. This study explored the epidemiological, clinical, and microbiological features of vaginal candidiasis in diabetic women referred to health and treatment centers in Kermanshah in 2023. Methods: This cross-sectional descriptive study was conducted on 215 diabetic women. A questionnaire was prepared for each participant. The samples were examined microscopically and cultured on Sabouraud dextrose agar (SDA). To identify different species of Candida (C.), various complementary tests were performed, such as the germ tube and differential sugar absorption test (API). A sensitivity test was applied to positive samples by the broth macrodilution method. Data were analyzed using the chi-squared test in SPSS. Results: Out of the 215 vaginal swabs investigated, 66 specimens were Candida-species positive (30.7%). 11.6% of participants were diagnosed with candidal vulvovaginitis by direct microscopic examination and 20.9% by culturing on SDA. The Candida species isolated were: C. albicans with 36 cases (54.5%), C. glabrata with 14 cases (21.2%), C. tropicalis with 9 cases (13.6%) and C. parapsilosis with 7 cases (10.6%). All species isolated showed the same sensitivity to the antifungal drugs used. Conclusion: The culture method was more sensitive than the direct microscopic examination. C. albicans was the most prevalent species isolated from patients. Non-albicans species were not prevalent.